2018
DOI: 10.1097/mcc.0000000000000477
|View full text |Cite
|
Sign up to set email alerts
|

Approaches and techniques to avoid development or progression of acute respiratory distress syndrome

Abstract: There is potential for improvement in the management of patients admitted to intensive care unit to reduce ARDS incidence. Apart from nonspecific measures, prevention of ventilator-induced lung injury and patient self-inflicted lung injury are of major importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
0
6
0
3
Order By: Relevance
“…5,6 Despite considerable research efforts, established therapeutic strategies for ARDS are limited. 7 Antiplatelet drugs, including aspirin and P2Y12 receptor inhibitors, are commonly used for secondary prevention of atherothrombotic events in patients with cardiovascular diseases. Aspirin and clopidogrel (P2Y12 receptor inhibitor) also reduce systemic inflammation and platelet-leukocyte coagulation, both of which are implicated in ARDS pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Despite considerable research efforts, established therapeutic strategies for ARDS are limited. 7 Antiplatelet drugs, including aspirin and P2Y12 receptor inhibitors, are commonly used for secondary prevention of atherothrombotic events in patients with cardiovascular diseases. Aspirin and clopidogrel (P2Y12 receptor inhibitor) also reduce systemic inflammation and platelet-leukocyte coagulation, both of which are implicated in ARDS pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic corticosteroids may alleviate the inflammation and lung edema, but ideally should be used for as short duration of treatment as possible 25 . Clinical studies demonstrated that corticosteroid was applied to 28 (20%) patients with severe COVID‐19 infection, for example, methylprednisolone at 40–80 mg daily for 5 days on average (IQR: 3–8 days) 1,6 .…”
mentioning
confidence: 99%
“…There is still an urgent need for specific therapy for ALI/ARDS, since almost all promising candidates have failed to prove beneficial in clinical trials 25 . For example, Cisatracurium as one of neuromuscular blockers failed to improve the prognosis of patients with ARDS in several clinical trials 26 .…”
mentioning
confidence: 99%
“…Increasing recognition of the adverse effects related to fluid overload in the ICU has led to more widespread adoption of conservative fluid management strategies ( 2 , 5 ). Patients with the acute respiratory distress syndrome (ARDS) are particularly vulnerable to adverse effects of fluid overload ( 6 8 ). Yet important knowledge gaps remain, including the optimal technique to assess overall volume status in ARDS ( 9 ).…”
mentioning
confidence: 99%